DEVELOPMENT OF MEANING IN WORDS AND SEMANTICS OF MEDICAL TERMS - Baxodir Turdiyevich Suyunov (European Science Publishing, 2024)
This article discusses the word and its semantic features, the smallest units of lexical meaning, as well as the semantics and etymology of some Uzbek medical terms. In this regard, the authors purposefully used scientific sources in Uzbek and Russian, as well as various dictionaries and research works, turned to examples and evidence that distinguished these concepts and phenomena, and made appropriate scientific conclusions on the topic. In particular, based on the method of historical-simultaneous analysis, the semantics and etymology of Uzbek medical terms are convincingly revealed. For example, when analyzing the term “temiratki” (lichen) on the relevant facts, its gradual changes from the appearance of Mahmud Koshgari on the sofa to the present day are emphasized.
Keywords: lexeme, sememe, seme, component, term, parameter, layer, morphology, conversion, polysemy, structure.